Pelatihan Literasi Ekonomi dan Keterampilan Komunikasi Melalui Kegiatan Market Day di Sekolah - Tarigan, Fatin Nadifa; Ismayani; Zsazsa , Cut Sah Kha Mei; Elanda, Yochie; Rizki, Ainur; Kaifu, Yoshita (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Economic literacy and communication skills are essential competencies that help students understand business concepts and interact effectively in professional and social environments. Early exposure to these competencies is important to encourage students to apply economic principles and communication skills in real-life situations. Therefore, the Market Day activity was conducted to introduce students to the concept of micro, small, and medium enterprises (MSMEs) while improving their communication abilities through practical experience. This community service program integrates economic literacy education with communication training, including verbal and non-verbal communication, public speaking, product promotion, and customer service. The activity involved 30 students who were divided into several groups and participated in product planning, product creation, and direct selling activities over two days. Evaluation was conducted through observation and performance assessment during the activity. he results showed positive improvements in students' understanding of basic economic concepts and communication abilities. Approximately 83% of students demonstrated increased confidence in interacting with customers, while 78% showed better ability in explaining and promoting products effectively. In addition, students demonstrated greater creativity, teamwork, and enthusiasm. In conclusion, the Market Day program was effective in enhancing students' economic literacy and communication skills through practice-based learning experiences.